2006
DOI: 10.1038/sj.cr.7310050
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional diversity of DMRT1 (dsx- and mab3-related transcription factor 1) in human testis

Abstract: Recent advances in the evolutionary genetics of sex determination indicate that the only molecular similarity in sex determination found so far among phyla is between the fly doublesex, worm mab-3 and vertebrate DMRT1(dsx-and mab3-related transcription factor 1) /DMY genes. Each of these factors encodes a zinc-finger-like DNA-binding motif, DM domain. Insights into the evolution and functions of human DMRT1 gene could reveal evolutionary mechanisms of sexual development. Here we report the identification and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 26 publications
(25 reference statements)
0
16
0
Order By: Relevance
“…Current knowledge concerning the function of this gene for the moment does not reveal the significance of this expression pattern. Very recent studies on the human testis have evidenced that three different transcripts may be generated by alternative splicing for this gene, and that they show different expression levels in the testis (Cheng et al, 2006). These data probably reflect that regulation of DMRT1 expression is controlled by a complex mechanism and that different transcript isoforms may play different roles in gonadal development and function.…”
Section: Discussionmentioning
confidence: 90%
“…Current knowledge concerning the function of this gene for the moment does not reveal the significance of this expression pattern. Very recent studies on the human testis have evidenced that three different transcripts may be generated by alternative splicing for this gene, and that they show different expression levels in the testis (Cheng et al, 2006). These data probably reflect that regulation of DMRT1 expression is controlled by a complex mechanism and that different transcript isoforms may play different roles in gonadal development and function.…”
Section: Discussionmentioning
confidence: 90%
“…Here we have further shown that the DMRT1 genes have another characteristic conserved among phyla: a special alternative splicing. The alternative splicing events occurred 3′ to the DM domain of the diverse species, including Drosophila (dsx) (Burtis and Baker 1989), zebrafish (dmrt1) , the rice field eel (dmrt1) , chicken (DMRT1), and human (DMRT1) (Cheng et al 2006). Although alternative splicing is known to increase diversity of the proteomic world, evolutionary and functional significance for the vast majority of alternative splicing events is unknown (Kriventseva et al 2003).…”
Section: Discussionmentioning
confidence: 99%
“…In the case of DMRT1 , alternative splicing may also play a role in defining its function. DMRT1 is alternatively spliced in human testis (Cheng et al, 2006) and in the gonads of lower vertebrates (Sreenivasulu et al, 2002;Guo et al, 2005). Most recently this has also been shown for DMRT1 transcripts in embryonic chicken gonads, with a male specific splice variant detected at stage 31, the time of gonadal sex differentiation (Zhao et al, 2007).…”
Section: When Are Sex-determining Genes Operating?mentioning
confidence: 97%